SYNTHESIS AND INVESTIGATION OF THIN TiO2 FILMS, DOPED WITH COPPER NANOPARTICLES - Aleksander Kravtsov; Andrej Blinov; Svjatoslav Krandievskij; Elena Momot (Вестник Северо-Кавказского федерального университета)
Thin films of titanium dioxide, doped with copper nanoparticles, were synthesized by the method of deposition on the rotating substrate. The obtained films were dried at room temperature and at temperature of TiO2 calcination and studied by ellipsometry, spectrophotometry and infrared spectroscopy. The concentration of copper sol in the solution for producing films affects the thickness of the resulting coating films and their refractive index. Adding copper nanoparticles in the titanium dioxide films leads to the appearance of absorption bands at 650 - 750 nm.